TINJAUAN YURIDIS KEJAHATAN SIBER METODE SKIMMING MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Septiono, Aris Aris (Hukum dan Dinamika Masyarakat, 2025)
Cybercrime using the skimming method is an act of theft by copying data from a debit or credit card by illegally taking information on the black strip on the back of the card (magnetic stripe). Currently, skimming perpetrators are threatened with criminal provisions in Article 46 relating to Article 30 of the Electronic Information and Transactions Law. The new Criminal Code (KUHP) with the enactment of Law Number 1 of 2023, which will come into effect on January 2, 2026, contains criminal acts of information and electronic transactions, which revoke several criminal articles in the Electronic Information and Transactions Law. How are the changes in the regulation of cybercrime using the skimming method in the new Criminal Code? This study uses a normative legal approach. The data source is secondary data in the form of laws and regulations, books, and journals. Research results, Article 332 of the new Criminal Code replaces Article 46 related to Article 30 of the Electronic Information and Transactions Law, there is a change in the fines of Article 332 paragraph (1) and paragraph (2) the threat of a category V fine of a maximum of IDR 500,000,000.00 (five hundred million rupiah), while paragraph (3) the threat of a category VI fine is a maximum of IDR 2,000,000,000.00 (two billion rupiah). In the new Criminal Code, Article 334 can also be applied to ensnare perpetrators of skimming crimes.